Symbolic violence and slavery:: Prudêncio's case in Machado de Assis' Memórias Póstumas de Brás Cubas (Ágora Journal, 2023)
Memórias Póstumas de Brás Cubas is a classic of Brazilian literature written by the most prestigious of our authors: Machado de Assis. In this paper we will analyze excerpts from the novel in which the former slave of Brás, Prudêncio, is found in the Valongo whipping a man who was his slave. Based on Pierre Bourdieu’s concept of symbolic violence, Roger Chartier’s representation and Sidney Chalhoub’s paternalism, we will analyze how Machado represented the fenomenon of a former slave aquiring captives and how does that relate with the inculcation of represantations through paternalistic notions that were present in Imperial Brazil’s slavery system.
Keywords: slavery; symbolic violence; Memórias P´óstumas de Brás Cubas